Perancangan dan Implementasi Sistem Penjualan Makanan Manis Berbasis Web Menggunakan Laravel dengan Fitur Kustomisasi Menu - Aldi Saputra; Arsito Ari kuncoro; Budi Hartono (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid advancement of information technology has driven digital transformation across various business sectors, including the culinary Micro, Small, and Medium Enterprises (MSMEs) industry. However, the majority of sweet food culinary businesses, such as Mirai Coffee and Snack, still rely on social media and manual instant messaging for transactions. Surveys indicate that 60% of customers encounter issues with slow response times and incorrect custom order recordings, resulting in 3 to 5 order errors per month due to human error. This study aims to design and implement a web-based sweet food sales system using the Laravel framework, featuring dynamic menu customization (such as adjustments for size, sweetness level, and topping variants). The system was developed using the Waterfall method, which includes requirements analysis, database design, code Implementation (PHP, MySQL), and Testing. The expected outcome is an integrated E-Commerce platform capable of automating custom price calculations in real-time, minimizing data entry errors, and systematically improving operational service efficiency from 10–15 minutes to instantaneous.